Synthesis and characterization of carbon microspheres from rubber wood by hydrothermal carbonization - Khan, Tanveer Ahmed; Kim, Hyun-Joong; Gupta, Arun; Saidatul Shima, Jamari; Rajan, Jose (Society of Chemical Industry, 2019)
Carbon has been a raw material for several thousands of industrial products and their production from various bioresources is an active area of research. This article details production of carbon microspheres from rubber wood via hydrothermal carbonization (termed as hydrothermal rubber wood carbon, HTRW carbon). Synthesis were coordinated in two sets: (i) in the first set, excess of water (20-40 × weight of biomass) was used in the hydrothermal process at 180-260 ⁰C for 3-9 hours and (ii) in the second set, water ratio was 25 – 35 × weight of biomass and the HTC reaction temperature fixed at 260 ⁰C. The chemical and physical characteristics of the products were studied by elemental analyzer, X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, gas adsorption studies, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The H/C and O/C atomic ratios of starting rubber wood was 1.78 and 0.85, respectively, which upon processing through the first strategy resulted in H/C ~0.78 and O/C ~0.29; thereby suggesting increased condensation under HTC.